2019
DOI: 10.1088/1361-6528/ab3566
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sulfur doping on fluorescence and quantum yield of graphene quantum dots: an experimental and theoretical investigation

Abstract: Graphene quantum dots (GQDs) are one of the most promising luminescent carbon derived nanomaterials decorated with multiple useful functional groups and remarkable optoelectronic properties. Heteroatom doping of hexagonal carbon sheet of GQDs is an effective strategy to tailor their properties to meet desired application. In this work, sulfur doped GQDs (S-GQDs) were synthesized by simply pyrolyzing citric acid (CA) as a source of carbon and 3-Mercaptopropionic acid as a source of sulfur dopant. The optimal re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 96 publications
(62 citation statements)
references
References 69 publications
(90 reference statements)
8
50
0
Order By: Relevance
“…Therefore, the development of appropriate non-toxic, water-soluble, and cost-effective fluorescent nanomaterials for targeted bioimaging of cancerous cells is highly desirable. Recently, graphene quantum dots (GQDs) and carbon dots (CDs) have emerged as a promising zero-dimensional fluorescent nanostructure for bioimaging applications by virtue of their fascinating properties such as high aqueous solubility, low cytotoxicity, high quantum yield, and effortless surface modification [21,22]. To expand their use in bioimaging applications for differentiating cancerous and non-cancerous cells, several reports have been consigned to covalent conjugation of FA with GQDs and CDs.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the development of appropriate non-toxic, water-soluble, and cost-effective fluorescent nanomaterials for targeted bioimaging of cancerous cells is highly desirable. Recently, graphene quantum dots (GQDs) and carbon dots (CDs) have emerged as a promising zero-dimensional fluorescent nanostructure for bioimaging applications by virtue of their fascinating properties such as high aqueous solubility, low cytotoxicity, high quantum yield, and effortless surface modification [21,22]. To expand their use in bioimaging applications for differentiating cancerous and non-cancerous cells, several reports have been consigned to covalent conjugation of FA with GQDs and CDs.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, another group described the N, S co-doped GQDs synthesis via carbonization of CA and L-cystine 96 . Likewise, the synthesis of sulphur doped GQDs has been reported by Kadian et al using CA and 3-mercaptopropionic acid (MPA) as raw precursors 20 . Liu described the pyrolysis of hexa-peri-hexabenzocoronene (Figure 2C) into multicolor photoluminescent GQDs 97 .…”
Section: Bottom-up Approachesmentioning
confidence: 97%
“…Chua and coworkers demonstrated the alteration of C60 into photoluminescent GQDs via cage-opening procedure using concentrated H2SO4, sodium nitrate, and potassium permanganate 83 . Over the past decade, several studies reported the synthesis of GQDs via carbonization or pyrolysis method 20,27,[84][85][86][87][88][89] . In line with this, firstly, Dong et al tuned the carbonization degree of carbon precursor (i.e., CA) for the preparation of blue fluorescent A D C B GQDs (Figure 2B) .…”
Section: Bottom-up Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, CDs are helpful for cell labeling, tracking cellular events, targeting specific cells due to their intrinsic fluorescent properties, and a vehicle for intracellular transport of drugs/genes [ 29 , 30 ]. Different nanomaterials such as graphene quantum dots (GQDs), carbon quantum dots (CQDs), fluorescence polymeric nanoparticles, partially graphitized core-shell carbon nanoparticles, and amorphous carbon nanoparticles are included in the family of CDs [ 29 , 31 , 32 , 33 , 34 ]. The surface functional groups of CDs provide easy conjugation with numerous therapeutic agents, prevailing in anti-viral applications [ 35 , 36 , 37 ].…”
Section: Introductionmentioning
confidence: 99%